2019
DOI: 10.3390/cancers11111798
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mutational Burden and Efficacy of Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis

Abstract: Tumor mutational burden (TMB) is a genomic biomarker that predicts favorable responses to immune checkpoint inhibitors (ICIs). Here, we set out to assess the predictive value of TMB on long-term survival outcomes in patients undergoing ICIs. We systematically searched PubMed, Embase, CENTRAL and clinicaltrials.gov from inception to 6 August 2019. We included retrospective studies or clinical trials of ICIs that reported hazard ratios (HRs) for overall survival (OS) and/or progression-free survival (PFS) accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 79 publications
5
83
1
Order By: Relevance
“…The clinical evaluation of TMB using blood specimens from the same institution differs greatly from the results obtained using tumor tissues, and the results of blood specimens show some instability. The conclusion drawn from this blood specimen is also inconsistent with the mainstream view that the high TMB patients should have better survival bene ts in NSCLC patients treated with ICIs [17,18]. The study author Chae YK et al also previously found a low correlation in ctDNA TMB and tissue TMB in paired patient samples [41].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The clinical evaluation of TMB using blood specimens from the same institution differs greatly from the results obtained using tumor tissues, and the results of blood specimens show some instability. The conclusion drawn from this blood specimen is also inconsistent with the mainstream view that the high TMB patients should have better survival bene ts in NSCLC patients treated with ICIs [17,18]. The study author Chae YK et al also previously found a low correlation in ctDNA TMB and tissue TMB in paired patient samples [41].…”
Section: Discussionmentioning
confidence: 76%
“…Currently, TMB is mainly studied as a predictive biomarker for ICIs treatment response [15,30]. Recent studies have concluded that in patients with higher TMB, the survival bene t of patients receiving ICIs is better than that of patients receiving chemotherapy alone, but in patients with low TMB, the survival bene t of ICIs is not statistically signi cant [17,18]. In this study, we did not group patients according to TMB value, but grouped according to lung cancer types, treatment methods, detection methods, test samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, the expression of MHC-II molecules was also detected on tumor cells and shown to correlate with T cell infiltration and the therapeutic response to CPI, indicating the presence of alternative antigen presentation pathways [87,88]. Notably, a lack of appropriate levels of tumor-specific antigen forms another important intrinsic resistance pathway against CPI [89]. In another screen, for key components determining the susceptibility of tumor cells to adoptively transferred effector cells, the GTPase Cdc42 was identified as a key factor in preventing CTL-induced cell death via MAPK signaling and posttranscriptional Bcl-2 stabilization [90].…”
Section: Tumor Cell Intrinsic Primary Resistance Mechanismsmentioning
confidence: 99%
“…The relationship between TMB and response to immunotherapy is explained by the generation of neoepitopes typical of tumors with many mutations that become a target for antigen presentation and powered CTLs activity [15].…”
Section: Introductionmentioning
confidence: 99%